Adherence to the ISHLT Protocol for the Referral of Patients with Idiopathic Pulmonary Fibrosis to the Transplantation Center among of Czech Centers for Interstitial Lung Diseases - Martina Sterclova; Martina Doubkova; Lubica Sykorova; Vladimir Bartos; Monika Zurkova; Vladimira Lostakova; Radka Mokosova; Martina Plackova; Ladislav Lacina; Michaela Cimrova; Radka Bittenglova; Pavlina Lisa; et al. (Pulmonary Medicine)
There are limited data on referral rates and the number of patients with idiopathic pulmonary fibrosis (IPF) who are eligible for lung transplantation. The aim of the present study was to assess adherence to the consensus of the International Society for Heart and Lung Transplantation (ISHLT) for the referral of patients with IPF among Czech interstitial lung disease (ILD) centers. Czech patients who were diagnosed with IPF between 1999 and 2021 (n=1584) and who were less than 65 years old at the time of diagnosis were retrospectively selected from the Czech Republic of the European Multipartner Idiopathic Pulmonary Fibrosis Registry (EMPIRE). Nonsmokers and ex-smokers with a body mass index (BMI) of <32 kg/m2 (n=404) were included for further analyses. Patients with a history of cancer <5 years from the time of IPF diagnosis, patients with alcohol abuse, and patients with an accumulation of vascular comorbidities were excluded. The trajectory of individual patients was verified at the relevant ILD center. From the database of transplant patients (1999-12/2021, n=541), all patients who underwent transplantation for pulmonary fibrosis (n=186) were selected, and the diagnosis of IPF was subsequently verified from the patient’s medical records (n=67). A total of 304 IPF patients were eligible for lung transplantation. Ninety-six patients were referred to the transplant center, 50% (n=49) of whom were referred for lung transplantation. Thirty percent of potentially eligible patients not referred to the transplant center were considered to have too many comorbidities by the reporting physician, 19% of IPF patients denied lung transplantation, and 17% were not referred due to age. Among Czech patients with IPF, there may be a larger pool of potential lung transplant candidates than has been reported to the transplant center to date.